THE EFFECT OF EDUCATION LEVEL, COMPETENCE, AND WORK EXPERIENCE ON EMPLOYEE PERFORMANCE AT POLICE CENTRAL JAVA - Anisa Windani; Muhammad Ricza Irhamni; Yayan Rangga Saputra (Universitas Wahid Hasyim Semarang, 2023)
The purpose of this study was to analyze the effect of the level of education, competence and work experience on employee performance. The research data is primary data with a questionnaire as a tool for collecting it. The sample for this study was police officers at the Central Java Regional Police Office, Itwasda Division. The sampling method for this research is probability sampling, with a total sample of 65 people. Data analysis methods used include data quality tests (validity and reliability), classical assumption tests (normality, heteroscedasticity, multicollinearity), multiple linear regression analysis, hypothesis testing (partial T test), coefficient of determination. The results showed that the variable level of education had no positive and significant effect on employee performance, while the competency variable had a positive and significant effect on employee performance and the work experience variable had no positive and significant effect on employee performance. From the results of testing the coefficient of determination Adjusted R Square obtains a score of 34.9 where this figure includes the influence of the variable level of education, competence and work experience on employee performance simultaneously. The suggestions given should be able to optimize performance and be able to assist further researchers in filling out the questionnaire because the answers given are very valuable for researchers. Then for further researchers to be more detailed in conducting research as well as being able to add research variables from learning factors and beliefs then add the number of samples and research in other objects or areas